2008
DOI: 10.1515/reveh.2008.23.2.91
|View full text |Cite
|
Sign up to set email alerts
|

Setting Prudent Public Health Policy for Electromagnetic Field Exposures

Abstract: Electromagnetic fields (EMF) permeate our environment, coming both from such natural sources as the sun and from manmade sources like electricity, communication technologies and medical devices. Although life on earth would not be possible without sunlight, increasing evidence indicates that exposures to the magnetic fields associated with electricity and to communication frequencies associated with radio, television, WiFi technology, and mobile cellular phones pose significant hazards to human health. The evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 85 publications
0
17
0
3
Order By: Relevance
“…It has been argued that the current approach in which a scientifically sound conclusion on health risk of a specific exposure is based on review of all available studies and if deemed necessary, subsequent amendment of protection strategies renders this debate open to criticism and controversy, which is routinely exploited by interest groups to prevent introduction of measures to reduce exposure levels (Carpenter and Sage, 2008;Genuis, 2008). This has been especially persistent in EMF research due to the intransigent disbelief of some vocal scientists and by delayed EMF legislation by injection of confusion and doubt into the scientific debate by focusing on uncertainties and deflecting attention from harm potential by vested interests (The International Commission for Electromagnetic Safety, 2006;Genuis, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been argued that the current approach in which a scientifically sound conclusion on health risk of a specific exposure is based on review of all available studies and if deemed necessary, subsequent amendment of protection strategies renders this debate open to criticism and controversy, which is routinely exploited by interest groups to prevent introduction of measures to reduce exposure levels (Carpenter and Sage, 2008;Genuis, 2008). This has been especially persistent in EMF research due to the intransigent disbelief of some vocal scientists and by delayed EMF legislation by injection of confusion and doubt into the scientific debate by focusing on uncertainties and deflecting attention from harm potential by vested interests (The International Commission for Electromagnetic Safety, 2006;Genuis, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This has been especially persistent in EMF research due to the intransigent disbelief of some vocal scientists and by delayed EMF legislation by injection of confusion and doubt into the scientific debate by focusing on uncertainties and deflecting attention from harm potential by vested interests (The International Commission for Electromagnetic Safety, 2006;Genuis, 2008). It has been argued that, whether causality has been proven or not, the associations between EMF exposure and health effects are sufficiently strong to warrant actions to reduce exposure levels in the general population (Carpenter and Sage, 2008;Genuis, 2008). However, it is precisely the discussion and subsequent scientific testing of these uncertainties that are of the utmost importance for the correct interpretation of data on potential health effects of electromagnetic field exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electromagnetic fields are considered by some a source of potential health risks [WHO, 2004;Carpenter and Sage, 2008]. The discussion ranges from impaired well-being to carcinogenic effects and also touches regulatory issues.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, numerous investigators evaluated the bio-effects of microwaves at different levels to shed light on the precise mechanisms of microwave radiation interacting with the living organisms [3]. In this regard, several researchers reported that EMF radiation induced serious health outcomes in people who inhabit around Wi-Fi and cell phone sources [4][5][6]. Some studies have revealed that EMF radiation emitted from cell phone, Wi-Fi router and other sources induce infertility in male reproductive system by decreasing the quality of semen [7][8][9].…”
mentioning
confidence: 99%